Новая находка остатков урмиорниса из неогеновых отложений Украины - Уманская, А.С. (Вестник зоологии, 1973)
Distal epiphysis of tibia of a fossil bird from the genus Urmiornis was found by paleontological expedition of the Institute of Zoology of the Ukrainian Academy of Sciences at a distance of 1.5 km to the north from the village Morozovka, Belyaevskian district, Odessa region (the Khadzhibei estuary left bank). The bone was found in talus at the level of alluvial meotic sands (it was probably burried there) underlying immediately the early anthropogen rock mass. The bone found somewhat differs from the holotype from Maraga (Northern Iran) and probably one must not consider it to belong to Urmiornis maraghenus M e c q. The bird which the bone belonged to should be attributed to the order Grues F u r b r i n g e r, family'Gruidae Vigor s, genus Urmiornis M e c q., 1908. The species title — Urmiornis sp. remains disputable.